Understanding the framing of hydrogen technology: a cross-national content analysis of newspaper coverage in Germany, Saudi Arabia, UAE, and Egypt - Ali, Majid; Hagen, Lutz (Frontiers in Communication, 2025)
IntroductionThe implementation of national hydrogen strategies targeting zero-emission goals has sparked public discussions regarding energy and environmental communication. However, gaining societal acceptance for hydrogen technology poses a significant challenge in numerous countries. Hence, this research investigates the framing of hydrogen technology through a comparative analysis of opinion-leading newspapers in Germany, Saudi Arabia, the United Arab Emirates, and Egypt.MethodsUtilizing a quantitative framing analysis based on Entman’s framing approach, this research systematically identifies media frames and comprehend their development through specific frame characteristics. A factor analysis identified six distinct frames: Hydrogen as a Sustainable Energy Solution, Benefits of Economic and Political Collaboration, Technological and Scientific Challenges, Governance Issues and Energy Security, Industrial and Climate Solutions, and Economic Risk.ResultsThe findings reveal that newspapers frames vary significantly due to contextual factors such as national hydrogen strategies, media systems, political ideologies, article types, and focusing events. Specifically, German newspapers display diverse and balanced framing, in line with its pluralistic media environment and national emphasis on green hydrogen and energy security, while newspapers from MENA countries primarily highlight economic and geopolitical benefits aligned with their national strategies and state-controlled media environments. Additionally, the political orientation of newspapers affects the diversity of frames, particularly in Germany. Moreover, non-opinion articles in Germany exhibit greater framing diversity compared to opinion pieces, while in the MENA region, the framing remains uniform regardless of article type due to centralized media governance. A notable shift in media framing in Germany was found after a significant geopolitical event, which changed the frame from climate mitigation to energy security.DiscussionThis study underscores the necessity for theoretical and methodological thoroughness in identifying frames, as well as the considerable impact of contextual factors on the media representation of emerging sustainable technologies.